GROWTH PRAWNS (Macrobrachium rosenbergii De Man) WITH DIFFERENT WIDE SHELTER - Riri Agustina; Rusliadi '; Usman M. Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted for 30 days from september to october 2014 which was held at the Great Hall of Freshwater Aquaculture Sukabumi, West Java Province. The purpose of this study was to determine the growth rate and survival rate of prawns (Macrobrachium rosenbergi De Man) with extensive shelter different method used is the experimental method with completely randomized design (CRD) of the factor with 3 levels of treatment. Ie P1 spacious shelter 30% of the area of the container, broad P2 shelter 60% of the total container broad P3 shelter 90% .of the vast container.Best results showed that the spacious shelter of 90% growth in absolute weight (4.48 grams), the growth of the absolute length (4.11 cm), daily weight growth rate (2.40%), survival (97%) higher in comparison with treatment spacious shelter 60% and 30%. each. Water quality parameters are recorded as temperature 24-26º C, 7.45 to 8.83 pH, and dissolved oxygen between (7.7 to 8.17 ppm).Keywords: Prawns, spacious shelter , tokolan, growth